The dynamics of erythrocyte infection in bovine anaplasmosis: a flow cytometry analysis - Moretta, Rosalia Ester (2014)
Anaplasma marginale (A. marginale) is an obligate intracellular bacterium that infects bovine erythrocytes causing extravascular hemolysis and anemia. In the present work, we combine SYTO16 labeling of parasitized cells with the statistical power of flow cytometry to study the evolution of erythrocyte infection during bovine anaplasmosis.